PRACTICAL ASPECTS OF CORRUPTION PREVENTION IN UZBEKISTAN - Otajonov Abrorjon Anvarovich (International Journal of Business, Law and Political Science, 2025)
Objective: This study explores the practical aspects of corruption prevention in Uzbekistan by analyzing recent legislative initiatives, institutional reforms, and insights from the National Anti-Corruption Council meeting held in March 2025. Method: Employing a qualitative approach, the study reviews national legal frameworks, presidential decrees, and institutional policies, supported by content analysis of expert commentaries and international indexes. Results: The findings reveal that corruption in Uzbekistan stems from bureaucratic opacity, excessive administrative procedures, and limited public accountability. Despite the enactment of the 2017 Law on Combating Corruption and the 2019 Presidential Decree on legal culture, enforcement mechanisms and civic oversight remain underdeveloped. Moreover, the emergence of digital corruption necessitates adaptive, forward-looking measures. Novelty: This article contributes a novel perspective by shifting the focus from punitive strategies to systemic, preventive solutions in the unique context of Uzbekistan’s post-Soviet administrative structure. It underscores the importance of digital governance, legal education, and targeted capacity-building in addressing contemporary corruption threats.